Understanding Barriers to Immunisation Against Vaccine-Preventable Diseases in Pacific People in New Zealand, Aotearoa: An Integrative Review - Tafea, V; Mowat, R; Cook, C (CSIRO Publishing, 2022)
Introduction: Pacific people have an increased risk of hospitalisation if barriers to immunisation against vaccine-preventable diseases are not reduced. This research sought to determine what is known about the barriers to immunisations in Pacific people living in New Zealand and identify ways to reduce these barriers and inform health care. Aim: To identify the barriers to immunisation for Pasifika and to identify ways to reduce these barriers and inform health care. Methods: An integrative review was undertaken with databases searched for articles published between February 2021 and May 2021. The review follows the five-stage process of problem formulation; literature search; evaluation of data; data analysis and interpretation; and presentation of the results through discussion. Results: Twelve studies were included. Three themes were identified: Deprivation, Health Literacy (which covered understanding the importance of immunisation programmes, attitudes and beliefs and communication), and access to health care (including communication accessibility to health professionals and physical access). Discussion: This review has identified that barriers such as level of deprivation strongly influences immunisation uptake in Pacific people. The significance of government-led initiatives was shown to improve the rates of immunisation of Pacific children. Pacific people’s awareness of immunisation programmes and government campaigns are encouraged to incorporate ethnic-specific strategies in addressing barriers, such as bringing vaccinations to where Pacific people frequent, including churches, community hubs, and venues that parents can easily access.
Keywords: Barriers; Challenges; Immunisations; New Zealand; Pacific people; Pacifica; Vaccinations; Vaccine-preventable diseases